Atividade funcional dos fagócitos do colostro humano tratados por citocina e quimiocinas na presença de Escherichia coli enteroinvasiva (EIEC) - Pereira, Cláudia Cristina de Sousa (2016)
The limited ability of immune response of infants to several infectious agents is associated with the development stage of the system at birth, and at this stage the maternal immunity is imported. The resistance of the newborn infection depends on the protective factors contained in colostrum that are highly targeted to infectious agents of the maternal environment and probably are found by children during their first weeks of life. Several studies have reported that human milk and colostrum protect the child to a variety of potentially pathogenic agents, immunological and tumor diseases, but the mechanisms of action of these factors are still partially understood. O breast milk has numerous specific immunological factors and non-specific including antibodies, glycoconjugates, lipids, enzymes, cytokines, chemokines, between these IL6, RANTES and MCP-1. It also features cells that play an important protective role for a variety of infectious agents, but the mechanisms involved in the interaction of phagocytes and chemokines, and these cells work on infections enteroinvasive Escherichia coli (EHEC) is partially known. Thus, targeting a greater understanding of defense mechanisms conferred by breast milk, this study aimed to evaluate the immunomodulatory activity of the cytokine IL-6 and RANTES and MCP-1 chemokines in colostrum phagocytes in the presence of Escherichia coli enteroinvasive (EIEC). We collected 30 samples of colostrum from clinically healthy mothers, aged 18 and 40, with an approximate volume of 8 ml. It were evaluated in colostrum cells superoxide anion release, phagocytosis and bactericidal activity. It was observed in this study that the colostrum phagocytes in the presence of Il-6, RANTES and MCP-1 present a significant increase (p <0.05) on superoxide anion release, phagocytosis, and bactericidal activity. The results of this study confirmed the importance of superoxide anion in the microbicidal mechanisms of phagocytes colostrum associated with these immunomodulators. These data suggest that probably the functional activity of phagocytes modulated by IL-6, RANTES and MCP-1 extends to other pathogens, as well as enteroinvasive Escherichia coli (EIEC).